Is Norway immune to Dutch Disease? CGE Estimates of Sustainable Wage Growth and De-industrialisation - Erling Holmøy; Kim Massey Heide (Statistics Norway, Research Department, 2005)
Norway's petroleum wealth has become considerably more liquid and thereby visible to the public since the mid 1990s. In the policy debate transformation of wealth is often confused with ordinary income. Such a misconception may have contributed to de-industrialisation through real appreciation beyond what is sustainable in a long run perspective. Since re-industrialisation is typically considered difficult, it is important to estimate a norm for sustainable wage growth. In Norway the textbook model of the Small Open Economy (SOE) has often been used for this purpose. We argue that this model neglects important aspects of the Norwegian economy. Instead we use a large scale dynamic CGE-model to estimate sustainable paths for wage growth and the activity in the traded goods sector, especially manufacturing. Under plausible assumptions we find that about 0.5 percent annual reduction of manufacturing employment is sustainable. The real appreciation over the last 7 years has been substantially above a sustainable trend.
Keywords: F4; 330; Dutch Disease; multi-sector growth; dynamic CGE-modelling.